Promoting Marriage Experimentation: A Class Act? - Julie Nice (Washington University Journal of Law & Policy, 2007)
The last decade of federal welfare reform has produced a windfall of funding for social science research, especially for studies focusing on whether and how recipients move from welfare to work. More recently, the federal government has funded a new wave of programs designed to reshape the family structure of impoverished parents and children. The centerpiece of this new focus on the family is the Bush Administration’s initiative to promote marriage. This Essay considers both the new marriage promotion policies and related social science research. The key question about marriage promotion concerns the link between welfare policy and social science data, specifically focusing on what policymakers will learn from emerging data generated by this grand experimentation with the lives of poor families.
Keywords: Marriage law; Public welfare; Welfare recipients; Marriage – government policy; George W. Bush Administration; Social science research; United States